Osteoporosis detection using radiomorphometric examination and fractal dimensions through cone-beam computed tomography - Efie Mariyam Nursari; Bramma Kiswanjaya; Menik Priaminiarti; Hanna H Bachtiar-Iskandar (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Cone-beam computed tomography (CBCT) is becoming more widely used in the field of dentomaxillofacial radiography, but its utility for bone quality assessment is still limited. This study was conducted to describe the use of radiomorphometric examination and fractal dimensions (FDs) for osteoporosis risk detection through CBCT in elderly patients. Medical databases (PubMed, Scopus, Elsevier, and Directory of Open Access Journals (DOAJ)) were searched using the keywords osteoporosis, radiomorphometric, fractal dimension, and fractal analysis. The search limits applied were available full-text articles, publication years 2012-2021, and articles published available in English. Then, the articles included were systematically reviewed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. A total of four studies were included in this review. Seven radiomorphometric indices were used, and most indices were adopted from panoramic radiographs, such as the computed tomographycortical index, computed tomography mental index, computed tomography index, and four other indices along the mandible, which are the S (symphysis), A (anterior), M (molar), and P (posterior) indices. All of the radiomorphometric studies show similar results. These indices can identify osteoporosis-related changes and are useful as osteoporosis screening tools on CBCT. However, all FD studies show different methods and discover heterogeneous results. Radiomorphometric measurement methods in CBCT can be used to detect patients at risk for osteoporosis. The FD analysis method still finds heterogeneous research results, so it is recommended to standardize the method in terms of the shape, size, and location of the region of interest.